ANALISIS PENGARUH JAM KERJA TERHADAP PENDAPATAN TENAGA KERJA SEKTOR INDUSTRI PENGOLAHAN DI INDONESIA: SEBELUM, SAAT DAN SATU TAHUN COVID-19 - Yulia, Rahmi; Muharja, Fajri (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2025)
The manufacturing industry is a major component of Indonesia's GDP, showing a decline in its contribution to the country during the Covid-19 pandemic. The purpose of this study is to determine and analyze the Effect of Working Hours on the Income of Workers in the Manufacturing Sector in Indonesia: Empirical Evidence Before, During, and One Year After Covid-19. This study uses time series and cross-sectional data from 2019-2021 obtained from Sakernas. The analysis method used is panel data regression to test the relationship between variables. The results of this study indicate that the variables of average working hours, Covid-19 dummy, 1 year of Covid-19, city dummy, average age, education ratio, gender ratio, and marital status ratio have a positive and significant effect on the income of workers in the manufacturing sector before, during, and one year after Covid-19. In addition, the working hours dummy variable and the Java dummy variable have a negative and significant effect on the income of workers in the manufacturing sector before, during, and one year after Covid-19. These findings indicate that working hours, Covid-19, urban areas, the island of Java, and socio-demographics have an effect on the income of workers in the manufacturing sector in Indonesia.